Concentration of credit exposure as a significant source of risk in banking activities: The idea and methods of estimation - Sylwester Kozak (e-Finanse: Financial Internet Quarterly, 2015)
The simultaneous activation of many sources of risk can slow bank operations and even lead to bankruptcy. Credit risk is the greatest threat to the orderly functioning of a bank. To protect against its materialization banks spend nearly 90% of their total capital requirement. Concentration of credit exposure to single entities, as well as to single economic sectors, can be a source of additional risks. Estimation of the additional portion of the capital requirement in selected banks in Poland in 2008-2013 indicates that banks should assign additional 4% and 2% of the capital requirement to cover the risk of exposure concentrations in: respectively, individual entities and individual economic sectors. For banks with a retail profile more important was the risk of large exposures in individual economic sectors, and for banks with a corporate profile in individual entities. Estimates were carried out according to the procedure used by the Bank of Spain and the Bank of Slovenia, and the data derived from the annual financial reports of selected banks listed on the WSE.
Keywords: G22; G32; 330; Poland; banks; credit risk